2005
DOI: 10.1210/me.2004-0497
|View full text |Cite
|
Sign up to set email alerts
|

The Glucose-6-Phosphatase Catalytic Subunit Gene Promoter Contains Both Positive and Negative Glucocorticoid Response Elements

Abstract: Glucose-6-phosphatase catalyzes the final step in the gluconeogenic and glycogenolytic pathways. Glucocorticoids stimulate glucose-6-phosphatase catalytic subunit (G6Pase) gene transcription and studies performed in H4IIE hepatoma cells demonstrate the presence of a glucocorticoid response unit (GRU) in the proximal G6Pase promoter. In vitro deoxyribonuclease I footprinting analyses show that the glucocorticoid receptor binds to three glucocorticoid response elements (GREs) in the -231 to -129 promoter region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 109 publications
7
106
0
4
Order By: Relevance
“…Consistently, disruption of G6Pase activity leads to severe hypoglycemia [48]. Expression of the G6Pase catalytic subunit gene has been known for decades to be induced by GCs: Adrenalectomy disrupts G6Pase exression [105], whereas GC treatment of isolated hepatocytes leads to G6Pase mRNA induction, the effect of which is mediated by the immediate 5'-flanking region of its gene [106][107][108][109][110]. Indeed, three functional GR response elements (GREs) have been identified A c c e p t e d M a n u s c r i p t 11 within the first 200 bp of the G6Pase promoter [110,111].…”
Section: Molecular Control Of Gluconeogenic Enzyme Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, disruption of G6Pase activity leads to severe hypoglycemia [48]. Expression of the G6Pase catalytic subunit gene has been known for decades to be induced by GCs: Adrenalectomy disrupts G6Pase exression [105], whereas GC treatment of isolated hepatocytes leads to G6Pase mRNA induction, the effect of which is mediated by the immediate 5'-flanking region of its gene [106][107][108][109][110]. Indeed, three functional GR response elements (GREs) have been identified A c c e p t e d M a n u s c r i p t 11 within the first 200 bp of the G6Pase promoter [110,111].…”
Section: Molecular Control Of Gluconeogenic Enzyme Expressionmentioning
confidence: 99%
“…Expression of the G6Pase catalytic subunit gene has been known for decades to be induced by GCs: Adrenalectomy disrupts G6Pase exression [105], whereas GC treatment of isolated hepatocytes leads to G6Pase mRNA induction, the effect of which is mediated by the immediate 5'-flanking region of its gene [106][107][108][109][110]. Indeed, three functional GR response elements (GREs) have been identified A c c e p t e d M a n u s c r i p t 11 within the first 200 bp of the G6Pase promoter [110,111]. Interestingly, the GR seems to functionally cooperate with additional factors in this context, including HNF-1, HNF-4, and FOXO1, all of which are required for the full GC response of the G6Pase promoter [110][111][112].…”
Section: Molecular Control Of Gluconeogenic Enzyme Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids have been shown to enhance the binding of specific transcription factors, including FOXO1, peroxisome proliferative activated receptor alpha (PPARA), and HNF4A to the extended glucocorticoid regulatory unit of the Pck1 promoter [22]. Additionally, both Pck1 and the gene for glucose-6-phosphatase contain glucocorticoid receptor binding elements, allowing glucocorticoids to enhance gene expression [23,24]. The co-activator peroxisome proliferative activated receptor, gamma, coactivator 1 alpha (PPARGC1A) also activates Pck1 expression through specific interaction with HNF4A, without binding directly to the Pck1 promoter [25].…”
mentioning
confidence: 99%
“…Glucose-6-phosphatase (G-6-Pase) is the final gatekeeper of glucose efflux from cells and catalyzes the last step of gluconeogenesis (17). Previous studies have suggested that G-6-Pase contributes to the development of diabetes and its promoter has several elements in common with PEPCK (18)(19)(20). Insulin receptor substrate (IRS) proteins, including IRS-1, IRS-2 and IRS-4 also serve a critical role in the signal transduction of insulin (21).…”
Section: Introductionmentioning
confidence: 99%